Ergonomics and occupational health and safety : a cost-benefit analysis model - Ramos, Delfina Gabriela Garrido (2013)
The economic costs of occupational safety and health problems place a considerable burden on the competitiveness of both the public entities and the enterprises. Ergonomic problems at the workplace and bad work organization are part of the contributing risk factors to the above mentioned occupational safety and health problems. There are also considerable social costs of workplace accidents related to ergonomic and work organization risk factors. This paper aims to propose a model for the application of Cost-Benefit Analysis in Occupational Health and Safety, taking into account namely ergonomic aspects involved. A previous qualitative exploratory study was undertake n using the Delphi methodology to get some input from an expert panel in order to determine the most important factors which should be included in the model of cost-benefit analysis. This model permits to perform economic evaluations of risks and prevention initiatives from both the company and the society perspectives. It is an important tool to support managers and experts to make an economic analysis before the beginning of any ergonomic intervention project.